Undiagnosed hypertension and proteinuria in an outpatient population in Northern Ghana - Yakubu, Abdul-Subulr; Adam, Atiku; Ahadzi, Dzifa (International Journal of Research in Medical Sciences, 2024)
Background: There is an upsurge in chronic kidney disease incidence worldwide. Late presentation characterises chronic kidney disease in sub-Saharan Africa. Hypertension and proteinuria are independent risk factors for worsening kidney function, irrespective of the cause of the kidney disease. We assessed the prevalence and predictors of hypertension and proteinuria in an outpatient population in Northern Ghana. Methods: We retrospectively reviewed screening data among adults ≥18 years of age in two of Ghana’s Northern regions. The data retrieved included socio-demographic information, blood pressure recordings, urine dipsticks and fingerpick blood glucose levels. The data were analysed for the prevalence of hypertension and proteinuria in the participants. Binary logistic regression analysis was employed to identify the predictors of significant proteinuria in these participants. A p-value <0.05 was considered statistically significant. Results: Total 1018 participants were included in the study, comprising 50.5% males. The prevalence of uncontrolled hypertension was 28.1%, using a blood pressure cut-off value of ≥ 140/90 mmHg. Significant proteinuria (≥ 1+ or 30 mg/dl) was present in 10.7% of the participants. Hypertension (AOR 2.433, 95% CI 1.582-3.742, p<0.001) and hyperglycaemia (AOR 2.226, 95% CI 1.159-4.275, p=0.016) were independent predictors of the presence of significant proteinuria. Conclusions: Uncontrolled hypertension and proteinuria were common in this outpatient population in Northern Ghana. The cost-effectiveness of community-based screening for chronic kidney disease and its risk factors in low-resource settings like Ghana, with the aim to treat to improve outcomes, needs to be explored.